2016
DOI: 10.1111/ppl.12453
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of substrate specificity‐associated residues and Ca2+‐binding motifs in EF‐hand‐containing type II NAD(P)H dehydrogenases

Abstract: Most eukaryotic organisms, except some animal clades, have mitochondrial alternative electron transport enzymes that allow respiration to bypass the energy coupling in oxidative phosphorylation. The energy bypass enzymes in plants include the external type II NAD(P)H dehydrogenases (DHs) of the NDB family, which are characterized by an EF-hand domain for Ca(2+) binding. Here we investigate these plant enzymes by combining molecular modeling with evolutionary analysis. Molecular modeling of the Arabidopsis thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This is still the best-studied enzyme, which is active as a membranebound dimer (Feng et al, 2012;Iwata et al, 2012;de Vries et al, 1992) (Figure 14). Homologues have since been found in most eukaryotes, including plants (Hao and Rasmusson, 2016;Matus-Ortega et al, 2011;Melo et al, 2004;Rasmusson et al, 1999), where they generally work in addition to Complex I, some of them forming a bypass around it (Braun et al, 2014;Finnegan et al, 2004;Rasmusson et al, 2004Rasmusson et al, , 2008 (Figure 11). In plants, there are three groups of mitochondrial type II NAD(P)H dehydrogenases, encoded by NDA, NDB and NDC genes (see Table 2), where the NDA and NDB genes have been inherited from the mitochondrial endosymbiont, while NDC1 has been inherited from the plastid progenitor (Michalecka et al, 2003).…”
Section: Non-energy-conserving Nad(p)h Dehydrogenasesmentioning
confidence: 99%
“…This is still the best-studied enzyme, which is active as a membranebound dimer (Feng et al, 2012;Iwata et al, 2012;de Vries et al, 1992) (Figure 14). Homologues have since been found in most eukaryotes, including plants (Hao and Rasmusson, 2016;Matus-Ortega et al, 2011;Melo et al, 2004;Rasmusson et al, 1999), where they generally work in addition to Complex I, some of them forming a bypass around it (Braun et al, 2014;Finnegan et al, 2004;Rasmusson et al, 2004Rasmusson et al, , 2008 (Figure 11). In plants, there are three groups of mitochondrial type II NAD(P)H dehydrogenases, encoded by NDA, NDB and NDC genes (see Table 2), where the NDA and NDB genes have been inherited from the mitochondrial endosymbiont, while NDC1 has been inherited from the plastid progenitor (Michalecka et al, 2003).…”
Section: Non-energy-conserving Nad(p)h Dehydrogenasesmentioning
confidence: 99%
“…RBOHA, an NADPH oxidase that synthesizes extracellular superoxide (Groom et al, 1996 ), was identified as an interactor of CIPK31 in the study. Further examination revealed that the C‐terminal of CIPK31 interacts with the second EF‐hand motif (a Ca 2+ ‐binding motif) (Hao & Rasmusson, 2016 ) of RBOHA. Structure simulation implied interaction between the NAF domain of CIPK31 and the EF‐hand motif of RBOHA.…”
Section: Discussionmentioning
confidence: 99%
“…RBOHA, an NADPH oxidase that synthesizes extracellular superoxide (Groom et al, 1996), was identified as an interactor of CIPK31 in the study. Further examination revealed that the C-terminal of CIPK31 interacts with the second EF-hand motif (a Ca 2+ -binding motif) (Hao & Rasmusson, 2016) A previous study also reported that Ca 2+ addition to the membrane protein fraction activated ROS generation, implying that the RBOH EF-hand motif might bind with Ca 2+ to activate its enzyme activity (Nagano et al, 2016) and induce an ROS burst, maintaining immune homeostasis during plant-microbe interaction (Yuan et al, 2017). These findings implied that the CIPK31 NAF domain might interact with the EF-hand motif to inhibit Ca 2+ binding, hindering RBOHA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the CaND amino acid sequences contained the conserved FAD-binding domain (Figure S1) and all CaNDB sequences contained an EF-hand domain, which is characteristic of NDB proteins from other plants and the site of calcium binding [31][32][33]. Clustal alignments of the highly conserved NAD(P)H binding domains revealed no differences between the expected substrate preferences for chickpea NDs compared to Arabidopsis NDs, whereby all NDAs and NDBs (except NDB1) contained a glutamate residue that is characteristic of NADH preference at its binding site [34]. Additionally, like Arabidopsis, the chickpea NDB1 contained a glutamine at this site and is likely to preferentially bind NADPH (Figure S1).…”
Section: Gene Identificationmentioning
confidence: 99%